Student midwives' knowledge, skills and competency in relation to the active management of the third stage of labour: A correlational study - Fungai Muzeya; Hester Julie (AOSIS, 2020)
Background: Lesotho has been experiencing health challenges as indicated by its high maternal mortality ratio of 620 per 100 000 live births for the year 2010, which has been linked to its limited human resources. Objectives: The knowledge and skills of final-year student nurse-midwives related to the active management of the third stage of labour were determined. Method: A quantitative, descriptive survey design was used to conduct this study with 99 final-year midwifery students at four nursing schools in Lesotho using stratified sampling. The structured questionnaire collected data on the knowledge and self-reported competency. Subsequently, the controlled cord traction marks, extracted from the objective structured clinical examination (OSCE), were compared to the self-reported competency of these midwifery students using R software version 3.4.0. Results: The mean score for knowledge and the OSCE was 73.8% (n = 99) and 77.2% (n = 99), respectively. The majority of respondents (95.2%, n = 99) rated themselves highly in terms of the active management of the third stage of labour competency. There was no correlation between the self-reported competency and knowledge (r = 0.08, p = 0.4402), and self-reported competency and OSCE scores (r = −0.004, p = 0.01). Conclusion: The high mean scores for the knowledge and the OSCE indicate that the theoretical component of the curriculum on the active management of the third stage of labour was effective in equipping final-year midwifery students with knowledge and skills to carry out this competency.